“THE DICTIONARY OF GEOGRAPHICAL NAMES OF WESTERN REGIONS” AND THE HISTORICAL GEOGRAPHICAL NATURE OF TOPONYMS RELATED TO KAZAKHSTAN AND THE CENTRAL ASIAN REGION (Journal of Oriental Studies, 2025)
The Xinjiang People's Publishing House (新疆人民出版社), located in Urumqi, the center of the XUAR of the People's Republic of China, is a state-owned fundamental publishing house that publishes books in five languages (Chinese, Uighur, Kazakh, Mongolian, Kyrgyz). The publication of data and research on the history and culture of indigenous peoples, the historical geography of the region, the historical role and significance of Xinjiang and the Central Asian region during the “Great Silk Road” is one of the priorities of this publication. One of these fundamental works is “The Dictionary of Geographical Names of Western Regions” («西域地名词典»), published in 2001 in Chinese. This article examines in detail the etymology of historical place names related to Central Asia and Kazakhstan included in this dictionary, the period of their introduction into Chinese, as well as their geographical location and scale compared with other data.The purpose of the research is to consider geographical names in the “Dictionary of geographical names of Western regions” related to Central Asia and the Kazakh land using historical, comparative and etymological methods, as well as semantic analysis and systematization. Data from the Chinese dictionary is one of the new and relevant topics in our domestic toponymic science, which is why this is the novelty of this article. The following are the features of toponymic names related to our region, written in Chinese characters, their exact translation in our language and the Chinese original are shown, as well as reconstructed and descriptions of them are given.The unification and introduction into scientific circulation of existing toponymic names, which are translated in our language in different ways, testifies to the scientific and practical result of this work.Keywords: “Western regions”, geographical names, China, XUAR, Central Asia, Kazakhstan, historical toponyms.